2010
DOI: 10.1002/ss.367
|View full text |Cite
|
Sign up to set email alerts
|

Tenuous options: The career development process for undocumented students

Abstract: Undocumented students face a variety of legal restraints in their efforts to enter higher education in the United States. These same legal restraints are just as formidable at the end of their academic career. Career development and other student affairs professionals need to understand these legal restraints so they can maximize the chances that undocumented students have to achieve their educational and career goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…Attention to the career development of undocumented Latina/o students has been sparse, with only a handful of studies directly addressing this issue, and most focusing on college students (Ortiz & Hinojosa, 2010;Pabón López & López, 2009;Pérez et al, 2009;. The aim of this study is to understand whether Latina/o high school students' vocational outcome expectations, anticipated barriers, and postsecondary plans varied as a function of their immigration status.…”
Section: Discussionmentioning
confidence: 98%
“…Attention to the career development of undocumented Latina/o students has been sparse, with only a handful of studies directly addressing this issue, and most focusing on college students (Ortiz & Hinojosa, 2010;Pabón López & López, 2009;Pérez et al, 2009;. The aim of this study is to understand whether Latina/o high school students' vocational outcome expectations, anticipated barriers, and postsecondary plans varied as a function of their immigration status.…”
Section: Discussionmentioning
confidence: 98%
“…For many undocumented students, academic and work choices are limited by confusing or restrictive college admissions policies and lack of access to financial aid or scholarships (Perez, Cortes, Ramos, & Coronado, ). Furthermore, a lack of documentation paperwork limits students' ability to find legal employment and obtain a driver's license, which can directly affect the opportunities available to them on college campuses (e.g., work study, internships, and educational travel; Ortiz & Hinojosa, ). Financing college is a primary obstacle faced by undocumented students because current government policies restrict students from accessing federal‐ and state‐based financial aid (e.g., grants or loan programs; Perez et al, ).…”
Section: Academic and Career Barriersmentioning
confidence: 99%
“…McWhirter, Ramos, and Medina () also found that Latino(a) high school students with undocumented status demonstrated lower vocational outcome expectations and anticipated more barriers to pursing higher education compared with students with legal documentation. Undocumented college students may also encounter distinct barriers during the career development process, such as limited career opportunities and increased risk of not being able to secure a job in one's area of education and training as the result of barriers (Ortiz & Hinojosa, ). Regardless of qualifications, undocumented students may not be able to legally enter the workforce after graduation (Ortiz & Hinojosa, ).…”
Section: Academic and Career Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some immigrant students will be undocumented. potentially leading to other issues related to financial aid status and career decision making (Gildersleeve & Ranero, 2010;Ortiz & Hinojosa, 2010).…”
Section: Exploring Immigrant Students' Experiencesmentioning
confidence: 99%